Analysis of using high-precision radiotherapy in the treatment of liver metastases regarding toxicity and survival - Voglhuber, Theresa; Eitz, Kerstin A.; Oechsner, Markus; Vogel, Marco M. E.; Combs, Stephanie E. (BMC Cancer, 2021)
Background: Hepatic metastases occur frequently in the context of many tumor entities. Patients with colorectal carcinoma have already developed liver metastases in 20% at the time of diagnosis, and 25–50% develop metastases in the further course of the disease and therapy. The frequent manifestation and the variable appearance of liver metastases result in an interdisciplinary challenge, regarding treatment management. The aim of this study was to evaluate high-precision stereotactic body radiotherapy (SBRT) for liver metastases. Methods: A cohort of 115 patients with 150 irradiated liver metastases was analyzed. All metastases were treated between May 2004 and January 2020 using SBRT. A contrast-enhanced computed tomography (CT) was performed in all patients for treatment planning, followed by image-guided high-precision radiotherapy using cone-beam CT. A median cumulative dose of 35 Gy and a median single dose of 7 Gy was applied. Results: Median OS was 20.4 months and median LC was 35.1 months with a 1-year probability of local failure of 18% (95%-CI: 12.0–24.3%). In this cohort, 18 patients were still alive at the time of evaluation. The median FU-time in total was 11.4 months and for living patients 26.6 months. 70.4% of patients suffered from acute toxicities. There were several cases of grade 1 and 2 toxicities, such as constipation (13.9%), nausea (24.4%), loss of appetite (7.8%), vomiting (10.4%), diarrhea (7.8%), and abdominal pain (16.5%). 10 patients (8.7%) suffered from grade 3 toxicities. Late toxicities affected 42.6% of patients, the majority of these affected the gastrointestinal system. Conclusion: SBRT is becoming increasingly important in the field of radiation oncology. It has evolved to be a highly effective treatment for primary and metastasized tumors, and offers a semi-curative treatment option also in the case of oligometastatic patients. Overall, it represents a very effective and well-tolerated therapy option to treat hepatic metastases. Based on the results of this work and the studies already available, high-precision radiotherapy should be considered as a valid and promising treatment alternative in the interdisciplinary discussion.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Hepatic metastases; High-precision radiotherapy; Liver metastases; Oncology; Outcome; SBRT; Stereotactic body radiation therapy; Survival; Toxicity